CRIMINAL LEGAL ENSURING OF SECURITY OF CRITICAL INFORMATION INFRASTRUCTURE OF THE RUSSIAN FEDERATION - R. Begishev, Ildar; I. Khisamova, Zarina; I. Mazitova, Guzel (Gênero & Direito, 2019)
The article considers the problems associated with the development of new state approaches to ensure the security of critical information infrastructure (hereinafter - the CII) in the context of the existence of threats to their information security, including computer attacks in its regard. We analyzed the main provisions of the Federal Law No. 187-FZ dated July 26, 2017 “On the Safety of the CII of the Russian Federation”.We disclosed the content and essence of the concept of “security of the CII”. It is justified that the security of the CII shall be based on the principles and methodology of ensuring national security. We have developed proposals to classify part of the subjects of economic activity as the CII subjects, as well as offered some additional mechanisms to increase the security of the CII. We proposed to develop and implement: the federal state standard of higher education in the direction of “safety of the CII”; retraining and advanced training courses in the direction of “safety of the CII”; a mechanism for improving the qualifications of officials of the CII subjects on various issues of ensuring its security; security insurance mechanism for the CCI; a mechanism for organizing international, all-Russian, regional and sectoral cyber orders at the CII objects. It has been established that the security of the CII directly depends on the correctness of decision-making in countering computer attacks, the speed and effectiveness of the actions of their entities. It is proved that the criminal law norm on liability for unlawful influence on the CII of the Russian Federation shall be changed